Relationship between performances of 10-time-repeated sit-to-stand and maximal walking tests in non-disabled older women. Issue 1 (December 2017) - Yanagawa, Naoko; Shimomitsu, Teruichi; Kawanishi, Masashi; Fukunaga, Tetsuo; Kanehisa, Hiroaki
Abstract Aim Sit-to-stand (STS) test is extensively used to assess the functionality of the lower body in elderly people. This study aimed to examine how the score of STS can be associated with that of maximal walking (MW) tests through a cross-sectional as well as longitudinal analysis for non-disabled older women. Method Times taken for a 10-time-repeated STS (STS time) and 5-m MW (MW time) were determined before (pre) and after (post) a 3-month body mass-based exercise program in 154 non-disabled women aged 60 to 79 years. In addition to the time scores, STS and MW power indexes (STS-PI and MW-PI, respectively) were calculated using the following equations: STS-PI = (body height − 0.4) × body mass × 10/STS time and MW-PI = body mass × 5/MW time. Results At pre- and post-intervention, STS-PI was significantly correlated to MW-PI, with higher correlation coefficients (r = 0.545–0.567, P < 0.0001) than those between the two time scores (r = 0.271–0.309, P < 0.001). The intervention significantly improved STS-time (13.6 ± 3.2 s at pre to 9.4 ± 1.8 s at post, P < 0.0001), MW time (2.4 ± 0.3 s to 2.2 ± 0.3 s, P < 0.0001), STS-PI (46.5 ± 12.5 to 65.7 ± 12.7, P < 0.0001), and MW-PI (112.1 ± 20.2 to 124.2 ± 24.4, P < 0.0001). There were significant correlations between the changes of STS and MW times (r = 0.281, P < 0.001) and between those of STS-PI and MW-PI (r = 0.366, P < 0.0001). Conclusion In elderly women, the performance of sit-to-stand task and its training-induced gain are associated with those of the maximal walking task. In addition, the current results indicated that translation of the performance scores of the sit-to-stand and maximal walking tasks to power indexes may be a useful approach for examining the association between the two tasks.